The Relationship Between Young Women's Knowledge About Dysmenorrhea and Its Treatment - Putri Sormin, Diana Annisa (Cattleya Darmaya Fortuna, 2022)
This study aimed to explore the relationship between young women's knowledge of dysmenorrhea and its treatment. A total of 200 women aged 18-25 years from various social and demographic backgrounds were involved in the study. Data were collected through a questionnaire that included questions about their knowledge of dysmenorrhea, symptoms experienced, and their preferred treatment strategies. The results of the analysis showed variations in the level of knowledge about dysmenorrhea and its treatment among the respondents. Findings also revealed that better knowledge about dysmenorrhea was significantly correlated with more effective treatment options. The implications of these findings in improving the understanding and management of dysmenorrhea in young female populations are discussed.